2019
DOI: 10.1177/1945892419850926
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Cytology as a Diagnostic Tool for Local Allergic Rhinitis

Abstract: Background Local allergic rhinitis (LAR) is characterized by chronic rhinitis with localized nasal allergic response to allergens in the absence of systemic immunoglobulin (IgE)-mediated disease assessed by skin prick test (SPT) or specific serum IgE level. Nasal provocation test (NPT) is the gold standard for the diagnosis of LAR. Nasal eosinophilia is a known inflammatory marker in allergic rhinitis. We hypothesized that nasal eosinophilia can be used as a screening tool for LAR. Objective To determine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Nasal cytology has highlighted a complex and heterogeneous landscape of NAR [4]. However, LAR does not seem to find a proper positioning in these classifications [60] because its pathogenetic aspect, consisting of local production of IgE and eosinophilia [61], tends to be confounded with an inflammatory feature, such as the one found in NAR with eosinophilia syndrome [60].…”
Section: Nasal Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal cytology has highlighted a complex and heterogeneous landscape of NAR [4]. However, LAR does not seem to find a proper positioning in these classifications [60] because its pathogenetic aspect, consisting of local production of IgE and eosinophilia [61], tends to be confounded with an inflammatory feature, such as the one found in NAR with eosinophilia syndrome [60].…”
Section: Nasal Cytologymentioning
confidence: 99%
“…Phothijindakul et al [61] developed a diagnostic algorithm for the diagnosis of LAR in confirmed NAR patients. The algorithm proposes the use of nasal cytology as a pivotal discriminator before the utilization of NAC due to its simplicity and contained costs.…”
Section: Nasal Cytologymentioning
confidence: 99%
“…The mixed cockroach NPT was started with mixed American and German cockroach at the concentration of 1:5000 weight per volume (wt/v) and 1:1000 wt/v. 12 All the procedure for NPT was similar with Der p NPT.…”
Section: Nasal Provocation Test To Mixed Cockroachmentioning
confidence: 99%
“…Phothijindakul et al found nasal cytology examination for nasal eosinophilia to be a useful screening tool with high sensitivity for diagnosing local AR. 3 Hamizan et al found that patients who were older, lacked comorbid asthma, and did not have self-reported inhalant allergy triggers were more likely to be diagnosed with true non-AR. 4 Another article from Hwang et al examined bisphosphonate use and chronic osteitis as a unique pathogenic factor for CRS.…”
mentioning
confidence: 99%